The dwarf mutation decreases high dose insulin responses in skeletal muscle, the opposite of effects in liver - Dominici, Fernando Pablo (2003)
The in vivo status of the proximal components of the insulin signaling system was investigated in skeletal muscle of Ames (Prop1 df/Prop1df) dwarf mice. The insulin-stimulated phosphorylation of the insulin receptor (IR) was reduced by 55% in Ames dwarf mice, while IR receptor protein content was not altered. Insulin-stimulated phosphorylation of IRS-1 and IRS-2 were decreased by 79 and 51%, respectively, while IRS-1 and IRS-2 protein levels were decreased by 66 and 43%. In addition, insulin-stimulated association of IRS-1 and IRS-2 with the p85 regulatory subunit of phosphatidylinositol (PI) 3-kinase was significantly reduced (by 80 and 41%, respectively), whereas insulin-stimulated PI 3-kinase activity was reduced by 66%. However, insulin-stimulated phosphorylation of Akt was slightly reduced (by 20%), suggesting that the attenuation of insulin signaling downstream PI 3-kinase may involve other signaling molecules. Our current results demonstrate that the Prop1 mutation decreases high dose insulin responses in skeletal muscle. This alteration is remarkable because these animals are hypersensitive to insulin and display an augmented response to insulin in liver at the same signaling steps. Reduced response to insulin in skeletal muscle could be important for the control of glucose homeostasis in these animals and could have implications in their extended longevity.